Robert Ludlum's The Bourne Dominion: Jason Bourne #9 - Lustbader, Eric; Ludlum, Robert, 1927-2001; Davidson, Jeremy (New York : Hachette Audio, 2011)
Searching for terrorists planning attacks on America's most strategic natural resources, Jason Bourne enlists the help of General Boris Karpov, the head of Russia's most feared spy agency, who has actually been tasked with Bourne's assassination.
Unabridged.
Compact discs.
Read by Jeremy Davidson.
Keywords: Bourne, Jason (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Audiobooks; Spy fiction